PENGARUH JUMLAH PENDUDUK DAN PERTUMBUHAN EKONOMI (PRODUK DOMESTIK REGIONAL BRUTO) TERHADAP UPAH MINIMUM KABUPATEN BOJONEGORO - Dados Susilowati; Happy Adianita (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Gross Regional Domestic Product (GRDP) and Regional Minimum Wage (UMR) are not always linear. For example, the increase in GRDP in Bojonegoro Regency is mainly caused by the oil and gas industry sector, while other sectors are lagging behind, so the increase in UMR may not be comparable. This research uses a quantitative approach and descriptive design to measure and explain the influence between independent variables (population and GRDP) and the dependent variable (minimum wage). The research population and sample include all data related to population, GRDP, and minimum wages in Bojonegoro Regency for the period 2009–2023 (time series) available from BPS. The data is processed using outlier filtering techniques. After that, statistical analysis was carried out using Eviews software: (1) normality test using the Jarque Bera method; (2) Autocorrelation test using the Durbin-Watson test if the DW DU value and (4-DW) DU value are equal; (3) Multicollinearity test based on the VIF value; (4) T test to test the partial effect by comparing the tcount and ttable values and a significance of 0.05; and (5) F test to test the simultaneous effect by comparing the fcount and ftable values and a significance of 0.05. In accordance with the research results, both variables contribute to the minimum wage in Bojonegoro district, namely 80.2%. This indicates that population and GRDP contribute a lot compared to other variables. The research results also explain that population and GRDP have a significant influence on the minimum wage in Bojonegoro district. As well as illustrating that the population is significant to the minimum wage in Bojonegoro district. Meanwhile, GRDP is not significant to the minimum wage.